Da margem à cadeia: adolescentes na criminalidade e o discurso veiculado pela veja - Godin, Patricia Zancanaro (2017)
The present work aims to analyze what effects of meaning emerge from the discourse of Veja magazine about adolescents, who commit an infraction act (ACAI), taking as theoretical perspective the french Discourse Analysis (AD), starting from Pêcheux (1990) 1995) (1999) (2014). In order to do so, we have worked with discoursive sequences (SD) extracted from six articles included in the magazine's General Publication, published between April 2013 and January 2016, which address the theme of crime during adolescence, so that, the discursive practice of this journal can be verified through linguistic materiality. Veja is the most sold magazine in Brazil, its expressive sales numbers make it representative nationally and its positions, related to national events, are significant. In this way, the journal is in a privileged place regarding the construction of public opinion, whether within the country or as a reference for foreign nations. The magazine, inserted in the Journalistic Discourse, acts in the institutionalization of meaning(s), and contributes to the construction of the social imaginary creating ways of seeing and interpreting reality. Thus, this work seeks to investigate the production of meanings of the journal, relating the linguistic to its constituent exteriority, so that it will be possible to understand the emergence of certain senses in detriment of others. It should be emphasized that the analysis seeks not only to point out evidences in the discourse of Veja magazine, but, above all, to work with the process of production of the evidences, identifying the marks of the ideological that determine the course of each discourse. It is believed that elucidating the discursive practices and knowing the process of construction and reproduction of the hegemonic discourses over the ACAI, will be a fundamental step in the elaboration and diffusion of an alternative, counter-hegemonic discourse and the construction of a generous look on these young people, in relation to their trajectories of risk, suffering and social neglect.